Efektivitas Program ITAC dalam Kerjasama Sister Province Provinsi Jawa Tengah dengan Queensland Tahun 2019-2021 - Farah Dila Puspitasarie; Mohamad Rosyidin; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The low quality standard pf education in Central Java in terms of standard of educators and ducation personel led to the initiation of the ITAC (International Training and Assessment Course) training program by Education and Culture Office with the Departement of Education and Training (DET), Queensland fpr vocational teachers in the Java Sister province cooperation. Central Java and Queensland are the background of this research. The problem that arises is how effective is the program in increasing the Sister province cooperation between Central Java and Queensland in the vocational Education?The purpose of the study was to determine the effectiveness of the Sister province through the implemented program. The efforts to answer the problems and research objectives are carried out using paradiplomacy theory and effectiveness indicators to analyze the effectiveness of the Sister province cooperation relationship that exists between Central java and Queensland. And to measure the effectiveness of the 2019-2021 ITAC program. The object of the research is the teachers of the revitalization of ITAC training participants in Central Java. The result showed that the Sister province cooperation was not effective. Especially in the implementation of cooperation programs where indicators of effectiveness driving factors such as aggrement upon strategy, regular contact, clear purpose and result, and monitoring and evaluation. It is recommended that the vovational teachers training program can continue to be carried out alternately with other vocational school teachers in Central Java so all the vocational school teachers in Central Java can have good quality , with improvements in the implementation training programs, especially on indicators aggrement upon strategy, regular contact, clear purpose and result, and monitoring and evaluation.